A learning robot for cognitive camera control in minimally invasive surgery - Wagner, Martin; Bihlmaier, Andreas; Kenngott, Hannes Götz; Mietkowski, Patrick; Scheikl, Paul Maria; Bodenstedt, Sebastian; Schiepe-Tiska, Anja; Vetter, Josephin; Nickel, Felix; Speidel, Stefanie; Wörn, Heinz; Mathis-Ullrich, Franziska; et al. (Surgical endoscopy and other interventional techniques, 2021)
Background  We demonstrate the first self-learning, context-sensitive, autonomous camera-guiding robot applicable to minimally invasive surgery. The majority of surgical robots nowadays are telemanipulators without autonomous capabilities. Autonomous systems have been developed for laparoscopic camera guidance, however following simple rules and not adapting their behavior to specific tasks, procedures, or surgeons. - Methods  The herein presented methodology allows different robot kinematics to perceive their environment, interpret it according to a knowledge base and perform context-aware actions. For training, twenty operations were conducted with human camera guidance by a single surgeon. Subsequently, we experimentally evaluated the cognitive robotic camera control. A VIKY EP system and a KUKA LWR 4 robot were trained on data from manual camera guidance after completion of the surgeon’s learning curve. Second, only data from VIKY EP were used to train the LWR and finally data from training with the LWR were used to re-train the LWR. - Results  The duration of each operation decreased with the robot’s increasing experience from 1704 s ± 244 s to 1406 s ± 112 s, and 1197 s. Camera guidance quality (good/neutral/poor) improved from 38.6/53.4/7.9 to 49.4/46.3/4.1% and 56.2/41.0/2.8%. - Conclusions  The cognitive camera robot improved its performance with experience, laying the foundation for a new generation of cognitive surgical robots that adapt to a surgeon’s needs.